2016
DOI: 10.3329/ajmbr.v2i3.30120
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stocking density on growth and production performance of monosex tilapia (Oreochromis niloticus) in ponds

Abstract: Stocking density is considered one of the important factors affecting fish growth. The study was aimed to compare the growth parameters of monosex tilapia at various stocking densities. The experiment was carried out during the period from 06 August to 22 December 2014. Three stocking densities were used as 125, 250 and 375 fish/dec and designated as treatment T 1 , T 2 and T 3 respectively each having two replicates. All the fishes were of same age group having average initial body weight of 1.34g. A commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
5
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 3 publications
9
5
1
4
Order By: Relevance
“…Hossain et al (2003) found that ammonia (NH4) in different treatments is varied from 0.004 to 0.077 mg/L that was insistent to the findings of present study. Similar study were conducted by Samad et al (2016); Islam et al (2017); ; Shabuj et al (2016); Rahman et al (2015); Ali et al (2016b); Rahman et al (2016) and Anka et al (2016); their results were also similar. Nitrite can be associated with ammonia concentration in the water body.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Hossain et al (2003) found that ammonia (NH4) in different treatments is varied from 0.004 to 0.077 mg/L that was insistent to the findings of present study. Similar study were conducted by Samad et al (2016); Islam et al (2017); ; Shabuj et al (2016); Rahman et al (2015); Ali et al (2016b); Rahman et al (2016) and Anka et al (2016); their results were also similar. Nitrite can be associated with ammonia concentration in the water body.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, nitrite concentration ranged from 0.01 mg/L to 0.03 mg/I, with the mean values of 0.013±0.01 mg/L, 0.01510.01 mg/L and 0.02710.01 mg/L, which was more or less similar to the findings of (Begum and Vijayaraghavan, 1999) who found that nitrite-nitrogen varied from 0.008 to 0.026 mg/L and 0 to 0.029 mg/L, respectively. Similar study were conducted by Samad et al (2016); Islam et al (2017); Rahman et al (2017); Rahman et al (2016) and Anka et al (2016); their results were also similar. In the present study, phosphate ranged from 0.6 to 1 mg/L which was more or less similar to the findings of Rahman (2003) who reported that PO 4 -P concentration varied from 0.78 to 2.5 mg/L in different treatments.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Padat tebar merupakan faktor penting yang harus dipertimbangkan dalam budidaya ikan. Beberapa studi telah mengevaluasi pengaruh padat tebar terhadap pertumbuhan dan metabolisme pada spesies ikan budidaya, terutama ikan-ikan lokal (Kusmini et al, 2017;Rahman et al, 2016;Prakoso et al, 2016;Joko et al, 2013;Li et al, 2012;dan Herrera et al, 2009). Kegiatan budidaya membutuhkan optimalisasi padat tebar sepanjang siklus hidup dari spesies yang dipelihara untuk menghindari aktivasi sistem stres dan konsekuensi kerugian ekonomi (Jia et al, 2016;Barton, 2002).…”
Section: Hasil Dan Bahasan Performa Pertumbuhanunclassified